Narrative, Identity, and the Map of Cultural Policy: Once Upon a Time in a Globalised World (Constance DeVereaux and Martin Griffin: Ashgate, 2013) - McQuaid, Paraic (Irish Journal of Arts Management and Cultural Policy, 2014)
The article reviews Narrative, Identity, and the Map of Cultural Policy: Once Upon a Time in a Globalised World, written by Constance DeVereaux and Martin Griffin (2013), which explores narrative as a conceptualisation within cultural policy discourse. Narrative, Identity, and the Map of Cultural Policy: Once Upon a Time in a Globalised World (Ashgate, 2013) is written by Constance DeVereaux of Colorado State University and Martin Griffin of University of Tennessee. In the book the authors propose a new academic approach to cultural policy, which they suggest has the potential to offer new ways of thinking and understanding the subject. The main focus of this new research approach is an exploration of narrative as a conceptualisation within cultural policy discourse. The authors view cultural policy as sitting within a framework of different narratives that are, at best, difficult to navigate